Sistem Pendukung Keputusan untuk Merekomendasikan Pilihan Laptop Menggunakan Metode Weighted Product - Fitra Fatimah Putri; Aldi Mulia; Budi Arifitama (Politeknik Negeri Batam, 2020)
In this modern and technological age, laptops have become a primary need or a primary need for everyone. Because laptops can help get some work done faster. The increased production of the laptop market with an assortment of specifications and brands may be confusing for users who just want to buy a laptop. This research proposes a decision support system to determine which laptop option is best according to the user's needs. Weighted Product method produces decisions by comparing between alternatives based on the function of preferences and weights that vary from each criterion where the result of the decision is determined from the rating results. The criteria used as an assessment to recommend laptop options are processor (C1), RAM (C2), storage (C3), and price (C4). From this developed system will produce a list of top 10 rankings based on the weight given or inputted by the user. With this system can help new people or users in determining the choice of the best laptop to use as needed.